American wood type 1828-1900 : notes on the evolution of decorated and large types and comments on related trades of the period - Kelly, Rob Roy, ....- (Saratoga : Liber Apertus Press, 2010)
The first and most authoritative history of wood type in the United States is now reissued in paperback. This book tells the complete story of wood type, beginning with the history of wood as a printing material, the development of decorated letters and large letters, and the invention of machinery for mass-producing wood letters. The 19th-century heyday of wood type is explored in great detail, including all aspects of design, manufacture, and marketing, and the evolution of styles. Many related trades interacted with wood type production; the book examines the influence of lithography, letterpress, metal-plate and wood engraving, sign painting and calligraphy, poster printing, and type-founding. Long out of print, the book is still regarded by scholars and designers as an invaluable resource for a rich legacy of typographic art. More than 600 specimens of wood type are classified and annotated, as are more than 100 specimens of complete fonts. This reissue includes a new foreword by David Shields, Design Curator of the Rob Roy Kelly Wood Type Collection at the University of Texas at Austin, discussing the renewed interest in the subject since the mid-1990s as well as ongoing research into the history of wood type.